(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Stagflation decimated the global economy throughout the 1970s and early 1980s. Recent empirical analysis suggests that the 1973 and 1979 oil crises were the catalysts for these high stagflationary periods. Other issues, such as whether stagflation is still a concern in the global economy, remain unresolved. Other than the price of oil, several factors contribute to stagflation. Humans can see that economies are susceptible to stagflation in a variety of ways using these measurements. Furthermore, even though stagflationary events occurred regularly between 1970 and 2010, the level of stagflation in the global economy tends to change over time. On the other hand, if stagflation develops, the magnitude increases. Our findings imply that stagflation is caused by a complex combination of factors and that oil price hikes’ traditionally large influence has decreased in the 2000s. Surprisingly, we found evidence that this impact has grown again at the sample’s conclusion. Today’s stagflation, on the other hand, is mostly driven by increasing interest rates and declining worker productivity. The main objective of this paper is learn more about Stagflation in World Economy-Impact on Indian Consumer Market. In the future, the problem is clear since people have been used to comparing productivity growth year over year or in shorter periods, typically using aggregates gross national product.